The Impact of The Implementation of Good Governance and Human Resource Competence on Budget Performance Based on Value for Money - Elysa Dwi Surani; Tutik Dwi Karyanti; Ardian Widiarto (Applied Accounting and Management Review (AAMAR), 2025)
This research aims to analyze the effect of implementing Good Governance and human resource competency on the performance of Value for Money based budgeting at BLU UPTD Trans Semarang. In the research, a sample of 90 employees was obtained using the determination method using Purposive Sampling. This research uses a quantitative approach with multiple linear regression analysis methods with the help of SPSS version 26. Data was obtained through distributing questionnaires to BLU UPTD Trans Semarang employees who were involved in budget management. The research results show that the implementation of Good Governance partially has an influence on Budget Performance with a Value for Money Concept, while Human Resource Competency has no significant effect on Budget Performance with a Value for Money Concept. Even so, simultaneous testing shows that the results of implementing good governance and human resource competence together have a significant effect on the performance of Value for Money based budgets.